Penanganan Ternak Qurban dan Metode Sembelih Halal - Khairul Murdani; Sri Rahayu; Djoko Subagyo; M. Masrianto; Hery Saputra; Khalidin (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2026)
This community service program aimed to improve community knowledge and practical skills in sacrificial animal handling and halal slaughtering practices in accordance with animal welfare principles and food safety standards. The program was conducted in Kayee Jatoe Village, Bandar Baru District, Pidie Jaya Regency, using socialization sessions, interviews, demonstrations, and hands-on slaughtering practices. The training covered the selection of eligible sacrificial animals, livestock handling techniques, ante-mortem and post-mortem inspections, halal slaughter procedures, and hygienic meat handling based on the principles of Safe, Healthy, Whole, and Halal (ASUH). The results indicated a significant improvement in participants' understanding and skills regarding proper animal selection, humane livestock handling, halal slaughtering techniques, and hygienic meat processing and distribution. Collaboration among the university, local government, and the community contributed substantially to the successful implementation of the program. Overall, the program enhanced the quality of Eid al-Adha sacrificial practices while promoting food safety and public awareness of halal livestock management.